Characterization of crack arrest phenomena in a modified 9Cr-1Mo steel - Sathyanarayanan S.; Moitra A.; Sasikala G.; Dasgupta A.; Saroja S.; Bhaduri A.K.; Raj B.; Singh V. (My University, 2025)
Crack arrest toughness (K1A) is a measure of the material's ability to stop a propagating cleavage crack. However, experimental evaluation of K1A from impact tests of small size specimens is often difficult due to the uncertainties involved in the determination of the two necessary parameters, namely, the crack arrest load (Parrest) and the crack arrest length (aarrest). In this study with Mod.9Cr-1Mo steel in normalized and tempered and in subsequent cold worked conditions, these two parameters and thus the K1A have been determined from instrumented impact tests carried out in the ductile-brittle transition temperature regime. While the Parrest has been directly determined from the load-displacement traces, the aarrest was inferred using an analytical technique, namely, the "key curve" method. The crack arrest phenomenon has been attributed to the cumulative effect of the blocking of the cleavage crack at the microstructural boundaries with high degree of misorientations as identified by scanning electron microscope and electron back scattered diffraction studies. The effect of cold work on the K1A has been found to be insignificant . Copyright © 1996-2011 ASTM.